Relationship mixes designs using a newly developed roller slab compactor against superpave gyratory compactor - Radzi, Hanani Mohamed; Muniandy, Ratnasamy; Hassim, Salihudin; Hua, Law Teik (Springer, 2024)
Roads and highways play essential roles in our lives. Compaction is the basic method with the most economical method of increasing road life and improving its load-bearing capacity. Even though the compaction costs are minimal, undoubtedly it can reduce future maintenance and extend years to the life of the road. Traditionally, laboratory asphalt mixture designs are based on Marshall Method and compacted using a 4.5 kg drop weight hammer, while in the field, the asphalt layer is compacted using a heavy-duty roller. Although the volumetric properties are reasonably accepted, the actual achievement of the roller slab compactor in the laboratory for purpose of mix designs and site is still farfetched. In recent years, the Superpave Gyratory Compactor (SGC) has come into play with a static load and kneading approach. This is still quite a mismatch with the roller compactor although the SGC procedure gives more consistent volumetric properties as compared with the Marshall Method. In this study, five gradations were tailored from the HMA AC14 mixture and analyzed using Bailey Method which conformed that HMA AC14 is the most recommended gradation that could be used for the entire research and to suit the fretted automatic roller compactor mix design. These five gradations were compacted with a newly developed fretted automatic Roller Slab Compactor (RSC) and compared with SGC in terms of mix design and performance testings. In comparison with SGC, the RSC showed a significant trend within required values for all the volumetric parameters which interpreted in a preliminary prediction equation. Similarly replicated in performance testings in fatigue and rutting between RSC and SGC, the aggregate orientation and distributions effect toward performance testing conditions in regardless to types of compactors. The RSC was performed significantly as laboratory compactor and proven rolling method to impose on asphalt mix designs.